La calidad de la colección bibliográfica de la sala infantil de la biblioteca municipal “Federico González Suárez” ubicada en el distrito metroplitano de Quito, fomenta en los niños y niñas que la visitan, el hábito lector. Año 2014 - Muñoz Proaño, María Elena (2014)
This thesis entitled: THE QUALITY OF LITERATURE COLLECTION OF CHILDREN'S ROOM MUNICIPAL LIBRARY "FEDERICO GONZALEZ SUAREZ" LOCATED IN THE DISTRICT OF QUITO Metropolitan, FOSTER CHILDREN IN THE VISIT, THE HABIT READER. YEAR 2014 has been structured and developed according to regulations Graduation National University of Loja. The general objective that guided the research was: Tend to strengthen children's libraries are collections of quality, to stimulate in children a love of books and develop the habit of reading as a source of information, recreation and positive use free time. The methods used for the preparation of this research work were: scientific, descriptive, inductive, deductive, Statistical Model. Techniques used were: survey of the staff of the Municipal Library "Federico González Suárez"; and children who attend the library, using a questionnaire designed for the purpose. Among the most significant results are: for 75% of library staff responded that characterize children's books collection is clear and good sized letter; 50% with appropriate language; 37% with entertaining stories and games; and the other 37% with clear contents. For 58% of children attending the library: the books they read in class are simple; to 52% are fun; to 40% are interesting; to 32% are boring; and 27% are complicated.